FORECASTING THE DEVELOPMENT OF AGRICULTURAL PRODUCTION IN THE CONTEXT OF FOOD SECURITY - Stepan Petrovich BURLANKOV; Mikhail Аleksandrovich ANANIEV; Alexandr Alexandrovich GAZHUR; Nadezda Vasilievna SEDOVA; Olga Mikhailovna ANANIEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The urgency of this study is substantiated by the problems related to forecasting the development of the national food market and the need to increase the capacity of the food security system. The problem becomes especially urgent due to the need to improve its sustainability and competitiveness. That is why in order to solve the problems of developing the national food security system, it is important to understand strategic benchmarks where the forecasts are considered to be especially important substantiated development benchmarks. The reality level of substantiating parameters of the food market development in the forecast models depends on the degree of accounting resources of the food commodity groups, and the opportunities for their forecasting are the basis for the reality of the forecast development scenarios. That is why the approach offered in the article assumes the solution to an urgent and timely problem. The goal of this article is to substantiate methodological approaches to commodity group forecasting of the food market development as the most objective in the system of strategic food security management, and based on this, to substantiate offers on developing the national food security system. Defining strategic long-term forecasts of the national food security system development and parameters of the food market based on them is an important area of scientific studies based on a comprehensive analysis of the agro-food market's activity, identifying the existing problems and developing offers on improving management instruments. The objects of the study are strategically important commodity groups of the production food subsystem of the national economy and food resources of the market.